2019
DOI: 10.1155/2019/7080941
|View full text |Cite
|
Sign up to set email alerts
|

The Spherical Shock Factor Theory of a FSP with an Underwater Added Structure

Abstract: A floating shock platform (FSP) is important experimental equipment for the antishock assessment of large-scale shipborne equipment. Generally speaking, the FSP is a square barge structure with a flat bottom. In order to satisfy the key index of the horizontal-to-vertical ratio of the impact environment, a special added structure is mounted to the bottom of the platform, and the impact environment is more complicated due to the added structure. Therefore, the spherical shock factor theory is proposed to analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…According to Figure 9a in the literature [13], the maximum error in the transv direction is 19.3%, with a slope of 0.094. Similarly, the maximum error in the vertica rection is 11.02%, with a slope of 0.11.…”
Section: Shock Environment Predictionmentioning
confidence: 88%
See 2 more Smart Citations
“…According to Figure 9a in the literature [13], the maximum error in the transv direction is 19.3%, with a slope of 0.094. Similarly, the maximum error in the vertica rection is 11.02%, with a slope of 0.11.…”
Section: Shock Environment Predictionmentioning
confidence: 88%
“…The simulation data and forecasting method presented in Equation ( 6) from the literature [13] were compared to normal-distribution-based interpolated confidence intervals for validation.…”
Section: A Shock Environment Prediction Methods Based On Normal Distr...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Wang et al [22] investigated numerically and experimentally the failure mode and dynamic response of a ship structure subjected to shock wave and bubble pulse. Jun et al [23] investigated the impact environment characteristics of floating shock platform subject to UNDEX. Young and Leonard [24] modeled and simulate a surface ship shock to UNDEX, the results showed that the cavitation effect must be taken into account in the ship shock simulation, and that cavitation volume must be large enough.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the shock testing machine, a floating shock platform can realistically simulate the shock environment of an actual warship facing underwater noncontact explosions. For these reasons, floating shock platforms, which were used as standard test devices for evaluating the shock resistance of large-scale warship equipment, have been widely used in navies around the world [3,4].…”
Section: Introductionmentioning
confidence: 99%